Transformational Leadership and Work Environment Shaping Turnover Intention Patterns: Kepemimpinan Transformasional dan Lingkungan Kerja yang Membentuk Pola Niat Berhenti Kerja - Doni Rusmadiansyah; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Employee retention remains a critical concern in human resource management, particularly in competitive business environments where organizations must maintain workforce stability to sustain operational continuity. Specific Background: PT Harian Bhirawa Surabaya experienced fluctuating employee turnover rates, with a recorded level exceeding acceptable organizational standards, raising concerns regarding leadership practices, workplace conditions, and employee attitudes toward their jobs. Knowledge Gap: Previous studies showed inconsistent findings regarding the relationships among transformational leadership, work environment, job satisfaction, and turnover intention, necessitating further empirical verification using alternative analytical approaches. Aims: This study aims to analyze the relationships between transformational leadership and work environment on turnover intention, as well as to examine the mediating role of job satisfaction among employees at PT Harian Bhirawa Surabaya. Results: The findings demonstrate that transformational leadership shows a significant negative relationship with turnover intention, while the work environment shows a significant positive relationship with turnover intention. Transformational leadership and work environment are both positively related to job satisfaction, and job satisfaction shows a negative relationship with turnover intention. Job satisfaction partially mediates the relationships between transformational leadership and turnover intention, as well as between work environment and turnover intention. Novelty: The study introduces the use of SmartPLS-based structural equation modeling to examine mediation relationships among organizational behavioral variables in the Indonesian media industry context. Implications: These findings provide managerial insights into designing leadership strategies and workplace arrangements to manage employee retention and organizational stability. Highlights: Leadership Behavior Demonstrates a Strong Inverse Relationship With Employee Withdrawal Tendencies. Workplace Physical and Organizational Conditions Correlate With Employee Retention Dynamics Through Satisfaction Mechanisms. Mediation Analysis Confirms Satisfaction as a Bridging Construct Linking Organizational Factors and Employee Resignation Tendencies. Keywords: Transformational Leadership, Work Environment, Turnover Intention, Job Satisfaction, Structural Equation Modeling